(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Because of their increased drug solubilization, long shelf life, and simplicity in preparation and administration, microemulsions are among the greatest options as innovative drug delivery systems. It is a microemulsion. Oil, water, and amphiphile liquid solutions that are optically isotropic and thermodynamically stable. There areas innovative medication delivery methods that enable regulated or sustained release for ocular, Medication administration methods include parenteral, topical, transdermal, and percutaneous. Using microemulsion, Because of their transparency and low viscosity, or more precisely because they are transparent compared to standard emulsions, stable thermodynamics Microemulsions are used in a wide variety of products, including Analytical applications, food, cutting oils, biotechnology, medicines, agrochemicals, and environmental cleansing, etc. This review paper's primary goal is to discuss microemulsions as medication delivery system that.